2020
DOI: 10.3390/vetsci7030112
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus johnsonii L531 Ameliorates Escherichia coli-Induced Cell Damage via Inhibiting NLRP3 Inflammasome Activity and Promoting ATG5/ATG16L1-Mediated Autophagy in Porcine Mammary Epithelial Cells

Abstract: Escherichia coli (E. coli), a main mastitis-causing pathogen in sows, leads to mammary tissue damage. Here, we explored the effects of Lactobacillus johnsonii L531 on attenuating E. coli-induced inflammatory damage in porcine mammary epithelial cells (PMECs). L. johnsonii L531 pretreatment reduced E. coli adhesion to PMECs by competitive exclusion and the production of inhibitory factors and decreased E. coli-induced destruction of cellular morphology and ultrastructure. E. coli induced activation of NLRP3 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…In the present study, TNF-α, IL-6, and IL-1β exhibited a sharp decrease in scFvs mixture group compared with the NC group (p < 0.05), indicating that scFvs have anti-inflammatory effects on mammary gland tissues. IL-8 and IL-18 contributed to neutrophil chemotaxis, which plays an important role in anti-bacterial immune response [34][35][36]. These studies indicated that suitable levels of five proinflammatory cytokines are vital for host defenses, whereas overmuch production can cause systemic inflammation and damage rather than protective effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, TNF-α, IL-6, and IL-1β exhibited a sharp decrease in scFvs mixture group compared with the NC group (p < 0.05), indicating that scFvs have anti-inflammatory effects on mammary gland tissues. IL-8 and IL-18 contributed to neutrophil chemotaxis, which plays an important role in anti-bacterial immune response [34][35][36]. These studies indicated that suitable levels of five proinflammatory cytokines are vital for host defenses, whereas overmuch production can cause systemic inflammation and damage rather than protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 and IL-18 are the proinflammatory molecules mediated by NFκB signal pathway in an inflammatory microenvironment. Previous studies showed that IL-8 and IL-18 contributed to neutrophil chemotaxis, which plays an important role in antibacterial immune response [34][35][36]. Inhibiting the production of TNF-α, IL-18, IL-6, IL-1β, and IL-8 is helpful to prevent inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic intervention is promising for modulating the NLRP3 pathways and has been verified by many studies. 154–157 NLRP3 activation was inhibited by probiotic supplementation, which stabilized osmotic pressure. 158 Lactobacillus also reduced ROS production by restoring the abnormal mitochondrial membrane potential, which alleviated NLRP3 activation.…”
Section: The Alleviative Effect Of Probiotics On Oxidation and Inflam...mentioning
confidence: 99%
“…The beneficial effects of a direct modulation of NLRP3 were also confirmed by a downregulation of pro-inflammatory cytokines, upregulation of anti-inflammatory players. These results have been also described feeding animals or treating cells derived from livestock with probiotics (1 × 10 5 CFU of Lactobacillus rhamnosus GR-1 and 3 × 10 5 –2 × 10 7 CFU of Lactobacillus johnsonii L531) with the aim of limiting the inflammatory damage of bacterial infections induced by Escherichia coli in porcine mammary epithelial cells, MAC-T cells and in a mouse mastitis model, or Salmonella typhimurium in IPEC-J2 cells [ 184 , 185 , 186 ]. The administration of these probiotics allowed limited bacterial adhesion to cells and bacterial alteration of cellular morphology, thus removing the first cause of ROS production and immune system activation.…”
Section: Food Components As Nlpr3 Modulatorsmentioning
confidence: 99%